Application of quality control circle activities to reduce the incidence of heart failure in peritoneal dialysis patients (降低腹膜透析透患者心力衰竭发生率中的品管圈实践) - QIAN Kai (钱凯); ZHAN Liuli (詹刘莉); XU Pengfei (徐鹏飞) (中西医结合护理)
Objective To explore the effect of Quality Control Circle(QCC) activities on reducing the incidence of heart failure among peritoneal dialysis(PD) patients. Methods A QCC team was established, with the activity theme of “reducing incidence of heart failure on PD patients”, On-site investigation, goal setting, formulating and countermeasures were carried out. Results The incidence of heart failure dropped from 13. 18% (29/220)before QCC management to 6. 78%(24/354) after QCC management. Conclusion QCC management is effective to reduce the risk of heart failure among PD patients. (目的 探讨品管圈(QCC)活动降低腹透患者心力衰竭发生率中的效果。方法 成立QCC小组, 确立“降低腹透患者心力衰竭发生率”为活动主题, 进行现况调查、目标设定、原因分析、对策拟定, 并实施各项对策。结果 腹透患者的心力衰竭发生率由活动开展前的13. 18%(29/220)降低至活动开展后的6. 78%(24/354)。结论 应用QCC活动对腹透患者进行容量管理控制, 可以有效降低腹透患者的心力衰竭发生风险。)